Music-Induced Analgesia in Healthy Participants Is Associated With Expected Pain Levels but Not Opioid or Dopamine-Dependent Mechanisms - Lunde, Sigrid Juhl; Vuust, Peter; Garza-Villarreal, Eduardo A.; Kirsch, Irving; Møller, Arne; Vase, Lene (Frontiers in Pain Research, 2022)
Music interventions accommodate the profound need for non-pharmacological pain treatment. The analgesic effect of listening to music has been widely demonstrated across studies. Yet, the specific mechanisms of action have still to be elucidated. Although the endogenous opioid and dopamine systems have been suggested to play an important role, a direct link has not been established. In addition, the involvement of placebo mechanisms is likely while largely unexplored. We examined the analgesic effect of music in healthy participants (n = 48) using a 3 × 3 within-subjects design with pharmacological manipulations and a matched, auditory control for music. Participants were exposed to thermal pain stimuli while listening to three auditory excerpts: music (active condition), nature sound (matched, auditory contextual condition), and noise (neutral control condition). The participants rated their expected and perceived pain levels in relation to each of the auditory excerpts. To investigate the involvement of the endogenous opioid and dopamine systems, the test session was performed three times on separate days featuring a double-blind randomized oral administration of naltrexone (opioid antagonist), haloperidol (dopamine antagonist), and an inactive agent (control). Our results support an analgesic effect of music. Contrary to current hypotheses, neither of the antagonists attenuated the effect of music. Yet, the participants' expectations for pain relief predicted their perceived pain levels during the auditory excerpts—even when controlling for a gradual learning effect. In conclusion, we demonstrate that the analgesic effect of music is at least partially mediated by expectations of an analgesic effect—a core mechanism in placebo effects—but not by opioid and dopamine-dependent mechanisms. Clinical Trial Registration www.clinicaltrials.gov, identifier: NCT03410563.